Endodontic Therapy in Mandibular First Premolar with Two Root Canals - Sookprome, Chulamanee (Journal of Health Science of Thailand, 2017)
One factor of the difficulties in root canal treatment is relating to anatomical variations in root canal morphology. Approximate 25 percent of mandibular first premolar teeth are considered to have more than one canal. This case report presents the successful five-year follow-up of a root canal treatment of mandibular first premolar with two canals. Prior to the initiation of endodontic treatment, the tooth and pulpal anatomy were essential to be assessed radiographically and clinically in order to manage the complex anatomy predictably successful. Good radiographs and proper modification of the access opening are the key factors to enhance intracanal preparation and obturation procedures.